Analisis dan Identifikasi Waste pada Proyek Jalan Tol Kayu Agung–Palembang–Betung STA. 75+000 – 84+825 dengan Pendekatan Lean Construction - Tri Hartono; Mohd. Isneini; Masdar Helmi; C. Niken DWSBU; Vera Agustriana Noorhidana (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Development in Indonesia continues to increase in line with growing community needs. In South Sumatra Province, one of the projects currently underway is the Kayu Agung – Palembang – Betung Toll Road. This study is expected to contribute to the development of Lean Construction methodology in Indonesia and provide practical recommendations for other infrastructure projects. The application of Lean principles in this project has significant potential to reduce waste and improve efficiency. The results of the study show that out of eight categories of waste, seven types of waste were identified. The two most dominant were Defects (24.14%) and Waiting (20.69%). The dominance of Defects indicates weaknesses in quality control, which leads to rework, cost overruns, and reduced resource efficiency. Meanwhile, the high level of Waiting illustrates a lack of synchronization in the workflow due to delays in material supply, ineffective coordination, and slow decision-making. The combination of these two factors has a direct impact on decreased productivity, schedule delays, and increased budgets. Therefore, this study emphasizes the need for stricter quality control and time management strategies through the application of Lean Construction principles.